[Kalendarz podziemny z 1986 r. wydany przez Solidarność Stocznia Gdańska] . Unofficial calendar for 1986 by the Gdańsk Shipyard Solidarity (NSZZ "Solidarność" Stocznia Gdańska, 1986)
Red and black print on white paper. The calendar includes a graphic image of Solidarity logotype inscribed in the symbol of infinity.